Aspergillus labruscus sp. nov., a new species of Aspergillus section Nigri discovered in Brazil - Maria Helena P. Fungaro (Nature Portfolio, 2017)
Abstract A novel fungal species, Aspergillus labruscus sp. nov., has been found in Brazil during an investigation of the fungal species present on the surface of grape berries (Vitis labrusca L.) for use in the production of concentrated grape juice. It seems to be associated to V. labrusca, and has never been recovered from Vitis vinifera. This new species belonging to Aspergillus subgenus Circumdati section Nigri is described here using morphological characters, extrolite profiling, partial sequence data from the BenA and CaM genes, and internal transcribed spacer sequences of ribosomal DNA. Phenotypic and molecular data enabled this novel species to be clearly distinguished from other black aspergilli. A. labruscus sp. nov. is uniseriate, has yellow mycelium, poor sporulation on CYA at 25 °C, abundant salmon to pink sclerotia and rough conidia. Neoxaline and secalonic acid D were consistently produced by isolates in this taxon. The type strain of A. labruscus sp. nov. is CCT 7800 (T) = ITAL 22.223 (T) = IBT 33586 (T).